PENGARUH GEL EKSTRAK BAWANG PUTIH (ALLIUM SATIVUM L.) TERHADAP JUMLAH SEL MAKROFAG PADA PENYEMBUHAN LUKA INSISI GINGIVA MARMUT (CAVIA PORCELLUS) - Poernomo, Hendri; Taha Ma'ruf, Mochammad (Interdental: Jurnal Kedokteran Gigi, 2020)
Surgical with an incision or tissue incision process can cause injury or tissue damage to the oral cavity, especially the gingiva. Wound healing can last a long time, this condition can increase the potential for complications such as infections and less blood supply. Garlic contains several active substances including flavonoids, tannins, phenols and alkaloids, and organosulfur compounds namely allicin. The content is believed to stimulate macrophage cells and help the work of macrophages in cleaning the wound area so that it accelerates into the phase of proliferation and wound healing. The research method was experimental laboratory research with a post-test design group. The results showed that the average number of macrophage cells in the control group CMC-Na 2% 97,50 cells, mean group of 40% garlic extract gel was 58,83 cells, mean group of 50% garlic extract gel was 18,00 cells, mean 60% garlic extract gel group was 7,83 cells. The results showed that there are significant differences (Ï <0,05) in the four study groups. Garlic extract gel concentration of 60% was more effective in reducing the number of macrophage cells in guinea pig gingival incision because of the percentage of active content.